Aflibercept therapy for polypoidal choroidal vasculopathy: short-term results of a multicentre study. Issue 9 (16th March 2015) - Koizumi, Hideki; Kano, Mariko; Yamamoto, Akiko; Saito, Masaaki; Maruko, Ichiro; Sekiryu, Tetsuju; Okada, Annabelle A; Iida, Tomohiro
Abstract : Background/aims: To investigate short-term outcomes of intravitreal aflibercept injections (IAIs) for polypoidal choroidal vasculopathy (PCV). Methods: 91 eyes of 88 consecutive patients with treatment-naive PCV examined at three university hospitals received IAI monthly for 3 months. One month after the third IAI, changes in best-corrected visual acuity (BCVA) and macular morphology were retrospectively evaluated. Additionally, possible baseline characteristics predictive of persistent retinal fluid were analysed. Results: The mean BCVA (logarithm of the minimum angle of resolution units) of the 91 eyes improved from 0.31 at baseline to 0.21 at 3 months (p<0.0001). The mean central retinal thickness and mean subfoveal choroidal thickness decreased from 323 μm and 270 μm at baseline to 185 μm and 232 μm at 3 months, respectively (p<0.0001 for both). Seventy-three eyes (80.2%) achieved a dry macula defined as absence of retinal fluid. Presence of the baseline characteristics of subretinal haemorrhage and greater size of the largest polyp were significantly associated with inability to achieve a dry macula (p=0.008 and 0.03, respectively). However, this association was not found on multivariate logistic regression. Of the 90 eyes that underwent indocyanine green angiography at 3 months, 43 eyes (47.8%) showed complete and 28 eyes (31.1%) showed partial resolution of polyps. Twenty-four eyes (24.4%) also showed partial regression of branching choroidal vascular networks. Conclusions: IAIs for the treatment of a large number of PCV eyes were found to improve both visual acuity and macular morphology over the short term.